Creating digital animations - Breen, Derek (John Wiley and Sons, 2016)
Are you the next great animator? All you need to create your own animated worlds is a computer connected to the Internet, a free Scratch account, and the fun projects you'll find inside the book! Follow simple steps to make your own characters, backgrounds, and actions